A Criatividade como processo pragmático na formação didática de professores de Arte - Lustosa, Ana Rita Cesar (2022)
This master's thesis approaches Creativity as a process in the formation of Art teachers, an important contemporary theme in the pedagogical debate. Its social relevance is present by providing possibilities for the training of teachers and students who need to be prepared to face the challenges posed by today's society. It is a research based on classical authors on the themes in question, characterized as exploratory, descriptive, explanatory. The methodology used was action research, supported by bibliographic research, participant observation, sensitive listening and field research. Two questionnaires, a diagnostic and an evaluative one, were applied to the group of Art teachers from the Municipality of Serra (ES), after the development of a teacher training program focused on creativity addressing the four languages of Art: Visual Arts, Theater, Dance, Music and also Literature. As required in the scientific methods, the data were analyzed using discourse analysis and content analysis and the conclusions reached are that theories and creative methods are still barely known and that there is interest and space for the development of the theme amongst the teachers from the Municipal Secretary of Serra, Espírito Santo.